(untitled) - Humphery-Smith, Ian (Hoboken, N.J., 2006)
Microbial pathogenesis at the proteome level Whole cell modeling Structural proteomics and computational analysis Biomolecular interactions Physiological proteomics Metabolic reconstruction using proteomics data While presenting the practical utility of proteomics data, the text is also clear on the field′s current limitations, pointing to areas where further investigation is needed. Offering a state–of–the–art perspective from internationally recognized experts, this text is ideally suited for researchers and students across the gamut of genomic sciences, including biochemistry, microbiology, molecular biology, genetics, biomedical and pharmaceutical sciences, biotechnology, and veterinary science.
Keywords: Microbial genomics,Gen của vi sinh vật